2018
DOI: 10.1534/genetics.118.300821
|View full text |Cite
|
Sign up to set email alerts
|

A Reassessment of Genes Modulating Aging in Mice Using Demographic Measurements of the Rate of Aging

Abstract: Many studies have reported genetic interventions that have an effect on mouse life span; however, it is crucial to discriminate between manipulations of aging and aging-independent causes of life extension. Here, we used the Gompertz equation to determine whether previously reported aging-related mouse genes statistically affect the demographic rate of aging. Of 30 genetic manipulations previously reported to extend life span, for only two we found evidence of retarding demographic aging: Cisd2 and hMTH1. Of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 71 publications
3
12
0
Order By: Relevance
“…We found that the effects of most lifespan-modulating interventions correspond to the displacement along such degeneracy manifolds on the longevity landscape. This is consistent with recent observations that most interventions in large-scale screens do not affect the mortality doubling rate (the rate of aging) (Liu and Acar, 2018;Nowak et al, 2018;Pedro de Magalhães et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…We found that the effects of most lifespan-modulating interventions correspond to the displacement along such degeneracy manifolds on the longevity landscape. This is consistent with recent observations that most interventions in large-scale screens do not affect the mortality doubling rate (the rate of aging) (Liu and Acar, 2018;Nowak et al, 2018;Pedro de Magalhães et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…For example, the range of recorded lifespans in our database for wild type strains of C. elegans under various conditions varies between 17.2 and 34.5 days at 15 degrees (avg: 23.66 days; SD: 4.36 days), and between 10.95 and 26 days at 20 degrees (avg: 18.8 days; SD 2.67 days) (for full histograms of WT lifespan at various temperatures, see http://www.synergyage.info/details/wildtype/ ). This was somewhat expected and is in line with literature reports as significant differences between the lifespan of controls is reported even in mice 25 . Similarly, if we consider the lifespan variation for one of the most well-known long-lived mutants, daf-2(e1370) worms live between 32.3 and 48.7 days at 15 degrees (avg: 37.7 days; SD: 4.52 days), and between 21.86 and 60.8 days at 20 degrees (avg: 39 days; SD: 7.98 days).…”
Section: Data Recordssupporting
confidence: 92%
“…example, the range of recorded lifespans in our database for wild type strains of C. elegans under various conditions varies between 17.2 and 34.5 days at 15 degrees (avg: 23.66 days; SD: 4.36 days), and between 10.95 and 26 days at 20 degrees (avg: 18.8 days; SD 2.67 days) (for full histograms of WT lifespan at various temperatures, see http://www.synergyage.info/details/wildtype/). This was somewhat expected and is in line with literature reports as significant differences between the lifespan of controls is reported even in mice20 . Similarly, if we consider the lifespan variation for one of the most well-known long-lived mutants, daf-2(e1370) worms live between 32.3 and 48.7 days at 15 degrees (avg: 37.7 days; SD: 4.52 days), and between 21.86 and 60.8 days at 20 degrees (avg: 39 days; SD: 7.98 days).…”
supporting
confidence: 92%